Ethical topics in international research with transgenic food - Rodríguez Yunta, Eduardo (Acta Bioethica, 2013)
This article reflects about the ethical issues generated in society by the production and use of transgenic or genetically modified food manufactured by biotechnology, such as: the commercial interests that guide this new technology, ecological risks, risks to human health, the possibility of introducing new plagues. Each country must regularize all aspects related to transgenic food in order to avoid risks and abuses by transnational companies and in order to protect vulnerable sectors of agriculture and livestock. Bioethical dialogue is proposed to balance both proponents, those who reject and those who support the production and use of genetically modified organisms for food, clarifying data with the help of science and promoting free information for an adequate environment for the possible development of this technology in the context of each country and community.